Ad Integrum Functional and Volumetric Recovery in Right Lobe Living Donors: Is It Really Complete 1 Year After Donor Hepatectomy?. Issue 1 (17th August 2015) - Duclos, J.; Bhangui, P.; Salloum, C.; Andreani, P.; Saliba, F.; Ichai, P.; Elmaleh, A.; Castaing, D.; Azoulay, D.
Abstract : The partial liver's ability to regenerate both as a graft and remnant justifies right lobe (RL) living donor liver transplantation. We studied (using biochemical and radiological parameters) the rate, extent of, and predictors of functional and volumetric recovery of the remnant left liver (RLL) during the first year in 91 consecutive RL donors. Recovery of normal liver function (prothrombin time [PT] ≥70% of normal and total bilirubin [TB] ≤20 µmol/L), liver volumetric recovery, and percentage RLL growth were analyzed. Normal liver function was regained by postoperative day's 7, 30, and 365 in 52%, 86%, and 96% donors, respectively. Similarly, mean liver volumetric recovery was 64%, 71%, and 85%; whereas the percentage liver growth was 85%, 105%, and 146%, respectively. Preoperative PT value (p = 0.01), RLL/total liver volume (TLV) ratio (p = 0.03), middle hepatic vein harvesting (p = 0.02), and postoperative peak TB (p < 0.01) were predictors of early functional recovery, whereas donor age (p = 0.03), RLL/TLV ratio (p = 0.004), and TLV/ body weight ratio (p = 0.02) predicted early volumetric recuperation. One‐year post‐RL donor hepatectomy, though functional recovery occurs in almost all (96%), donors had incomplete restoration (85%) of preoperative total liver volume. Modifiable predictors of regeneration could help in better and safer donor selection, while continuing to ensure successful recipient outcomes. Abstract : Though functional recovery occurs in almost all right lobe liver donors, the authors find that at 1 year post‐right lobe donor hepatectomy, only 85% of donors achieve ad integrum volumetric recovery.